"Kak s`eli petuha" i počemu - Benčić, Živa (Array, 2009)
The article analyses a short story by Evgeny Popov titled “How the Rooster Was Eaten” or, more precisely, analyses meanings which the rooster has in the text as a festive New-Year dish. Based on culinary binary oppositions that Claude Lévi-Strauss used to describe the nutritional habits of various European and non-European nations, the author of this article reduces the basic collision of Popov’s story to a dichotomy between the food of vegetable origin and the food of animal origin or, more concretely, to an opposition between a non-meat soup on the one hand and the rooster on the other as two opposed variants of the New-Year feast. The author also aims to show that the semantic opposition between vegetarianism and “carnivorousness” is multidimensional, i.e. that beside the sensory-corporeal it also includes many other dimensions of human existence: in the context of Soviet culture it points also to the opposition between the poor and the bourgeois, the ideologically acceptable and the ideologically unacceptable, the everyday and the festive, the profane and the sacred. The article, finally, aims to shed light on a deeper and today slightly forgotten layer of meanings that the rooster has had in opposition to the non-meat soup: the rooster is not just a profane-gourmet, but also a ritually sacrificial food that is prepared only for festivities as a token for a better future, i.e. as a symbolic trade for a future wellbeing and good fortune of the votive offerer.